1987
DOI: 10.1111/j.1365-2559.1987.tb02668.x
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric detection of B‐clonal excess in fine needle aspirates for enhanced diagnostic accuracy in non‐Hodgkin's lymphoma in adults

Abstract: Fine needle aspiration (FNA) cytology is a valuable aid to diagnosis and tumour staging in patients with non-Hodgkin's lymphoma. These tumours are often multicentric and involve sites such as the liver or the spleen which are not easily accessible to surgical biopsy. Particularly with splenic involvement, there is a diagnostic problem of morphologically distinguishing the lymphoma cells in an admixture of normal lymphocytes. Since most lymphomas in adults are of B-cell origin, we studied the diagnostic value o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…20 In another study, 37% of cases with normal or inconclusive findings on sFNA were diagnosed as ML by light chain analysis. 16 In our study the usefulness of ancillary techniques was demonstrated by confirmation of the diagnosis of ML by FC in 2 patients and by IHC in 3. It has been suggested that sFNA is useful for patients with splenic masses as compared to splenomegaly.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…20 In another study, 37% of cases with normal or inconclusive findings on sFNA were diagnosed as ML by light chain analysis. 16 In our study the usefulness of ancillary techniques was demonstrated by confirmation of the diagnosis of ML by FC in 2 patients and by IHC in 3. It has been suggested that sFNA is useful for patients with splenic masses as compared to splenomegaly.…”
Section: Discussionmentioning
confidence: 56%
“…2,4,9-11 Lymphoma has also been evaluated in some studies by this procedure. 15,16 However, there are very few reports on the use of sFNA for metastatic lesions of the spleen owing to the relative infrequency of these lesions 17 and fear of hemorrhagic complications. 18 Our analysis suggests that sFNA and sCB have good diagnostic accuracy, are fairly safe and can obviate the need for an open biopsy or splenectomy in the majority of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…Several more recent publications have reported much lower complication rates with smaller needle diameters (18 gauge or smaller) ( 5,6,16 ). Diseases that commonly affect the spleen can pose a diagnostic challenge to the clinician, radiologist, and pathologist, and the reported diagnostic accuracy of splenic biopsy varies, ranging between 84% and 90% ( 5,14,(16)(17)(18)(19)(20)(21).…”
Section: Search Strategymentioning
confidence: 99%
“…[28][29][30][31][32][33][34][35][36][37][38][39] The majority of the studies used the Working Formulation Classification of NHL. However, comparison of the studies was very difficult because classification was often in generic terms such as small cell NHL or large cell NHL.…”
mentioning
confidence: 99%